A Comparative Study of the Buddhist Approach to Organizational Behaviour Based on the Canonical Sources - Ranawakaarachchi, Padmasiri (Advances in Social Sciences Research Journal, 2019)
Abstract Organizational Behavior (OB) is one of the hot topics discussed in modern management and recognized as one of the most important factors for success of any organization. The interface between the behavior of individuals and the organization is known as the OB and it is the field of study devoted to understanding, explaining and ultimately improving the attitude and behavior of individuals and groups in organizations. In this connection the researcher has developed an OB model based on contemporary management thoughts. The aim of the research is to study the concepts relating to organizational behavior and compare Buddhist approach to organizational behavior based on canonical sources. The Buddhist teaching did not much focus on presenting very complex theories on human behavior like contemporary Western scholars who have developed various theories and models to interpret human behavior. Nevertheless the Buddhist doctrine was of more practical nature which addressed all the issues of human behavior of both laymen and disciples. The existence of the order of Saṅgha which is considered to be the oldest democratic organization in the world for more than 2500 years shows the soundness of the organization structure and the philosophy on which it was built. When studying the monastic order and the monastic discipline in depth one could understand the management skills of the Buddha and how He had applied Buddhist teachings in managing the monastic order. Thus the Buddhist approach to Organizational Behavior is well elaborated in the Vinayapiṭaka. Similarly the Buddhist teaching was focused on wellbeing of the family and the behavior of individuals. Sigālovādasutta alone can be considered as one of the most significant discourses for guiding the behavior of laymen. Similarly Parābava and Maṅgala are a few of the many suttas addressed almost all the issues one would come across in the family. As most of the economic activities are family based, behavior of the individuals and their traits such as attitudes, values, ethics and emotions had much impact on the economy and the society at large during that period. There are many discourses in the Suttapiṭaka which had clearly defined ways and means to change the behavior of individuals and disciplined them with firm changes in individual traits. It is interesting to note that some of the issues addressed by the United Nations to safeguard human rights had been identified and addressed through the pañcasīla and solutions for the most of the Sustainable Development Goals presented under ‘the 2030 Agenda’ too had been provided by the Buddha 2500 years ago. When studying the Canonical sources especially the Suttapiṭaka and Vinayapiṭaka with a view to compare the Buddhist perspective on organizational behavior against the contemporary management thoughts, it is evident that the Buddhist approach results in a permanent improvement in human behavior and the organization. Keywords: Contemporary Management, Organizational Behavior, Individual Traits, Monastic Order, Canonical Sources